HEALTH CONSEQUENCES AND SOCIAL IMPLICATIONS OF E-CIGARETTE USE IN ADOLESCENTS - Lepa, Zuzanna; Mateusz Sydor; Wojciech Plizga; Aleksandra Bułat (International Journal of Innovative Technologies in Social Science, 2026)
Background: E-cigarette use among adolescents has emerged as a critical global public health challenge. Although electronic nicotine delivery systems (ENDS) were initially promoted as a less harmful alternative to conventional cigarettes for adults, they have become a primary source of nicotine exposure among youth. Adolescence represents a neurodevelopmentally vulnerable period characterized by ongoing maturation of the prefrontal cortex and heightened sensitivity of reward systems, which increases susceptibility to nicotine addiction and its potential long-term health consequences.Methodology: A narrative review was conducted using literature identified through PubMed, Scopus, and Web of Science, encompassing recent original studies, systematic reviews, meta-analyses, and experimental models. The review synthesizes evidence from epidemiological, clinical, experimental, and neurobiological research to examine the biological, neurodevelopmental, cardiovascular, respiratory, and psychosocial effects of adolescent e-cigarette use. In addition, social determinants, marketing influences, regulatory frameworks, methodological limitations, and emerging research directions were considered to contextualize patterns of use and gaps in the current evidence base.Results: Available evidence indicates that e-cigarette use during adolescence is associated with structural and functional alterations in brain development, including disrupted synaptic plasticity, impaired executive function, increased vulnerability to nicotine dependence, and heightened risk of subsequent substance use and mood disorders. Cardiovascular effects include sympathetic nervous system overactivation, elevated blood pressure, endothelial dysfunction, oxidative stress, and pro-inflammatory responses, potentially predisposing adolescents to long-term cardiovascular disease. Respiratory consequences involve airway irritation, impaired mucociliary clearance, inflammation, and early signs of functional decline, with risks amplified among dual users of e-cigarettes and conventional cigarettes. Initiation and sustained use are strongly influenced by social factors, including peer norms, social media marketing, flavor availability, and socioeconomic disparities, which reinforce normalization of nicotine use. Despite growing evidence of harm, substantial heterogeneity in study designs, exposure assessment, product types, and reliance on self-reported data, along with limited longitudinal evidence, continues to constrain causal inference.Conclusions: Adolescent e-cigarette use poses significant neurodevelopmental, cardiovascular, respiratory, and psychosocial risks. Comprehensive public health strategies—including regulatory measures, preventive education, peer-based interventions, and equitable policies—are urgently needed to reduce nicotine initiation and dependence among vulnerable youth. Furthermore, large-scale longitudinal studies are essential to clarify long-term outcomes and guide evidence-based policies to protect adolescent health.